2015
DOI: 10.1021/jp510089s
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Phase Separation in Supported Pd–Au Catalysts

Abstract: SiO 2 -supported Pd−Au catalysts with Pd/Au molar ratios varying from 0.8 to 7.0 were used as catalysts for vinyl acetate synthesis under industrial conditions. Continued operation of the bimetallic catalysts at 150 °C led to the formation of the Pd 1 Au 1 phase in the particles, with the remaining Pd atoms forming Pd nanoparticles by leaching of Pd as acetate. The presence of these phases was monitored by X-ray absorption spectroscopy (XAS) of the used catalysts. Temperature-resolved in situ XRD of the reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, selective leaching may also occur during a catalytic reaction, which can alter the productivity and selectivity of the process. More recently, XAS has also been successfully employed to study the leaching of Pd from SiO 2 -supported bimetallic Pd/Au catalysts during the synthesis of vinyl acetate from ethylene, carbon monoxide and acetic acid [16]. Under industrially relevant conditions, exposure of the catalyst to acetic acid led to leaching of Pd from the alloy as palladium(II) acetate, leading In an earlier paper, we have found that a sample of 5% Pd/Al 2 O 3 undergoes leaching when it was exposed to a heated solution of aqueous ethanol [17].…”
Section: Direct Observation Of Catalyst Leaching (Operando Spectroscopy)mentioning
confidence: 99%
“…However, selective leaching may also occur during a catalytic reaction, which can alter the productivity and selectivity of the process. More recently, XAS has also been successfully employed to study the leaching of Pd from SiO 2 -supported bimetallic Pd/Au catalysts during the synthesis of vinyl acetate from ethylene, carbon monoxide and acetic acid [16]. Under industrially relevant conditions, exposure of the catalyst to acetic acid led to leaching of Pd from the alloy as palladium(II) acetate, leading In an earlier paper, we have found that a sample of 5% Pd/Al 2 O 3 undergoes leaching when it was exposed to a heated solution of aqueous ethanol [17].…”
Section: Direct Observation Of Catalyst Leaching (Operando Spectroscopy)mentioning
confidence: 99%
“…PdAu alloys can provide catalytic rates and selectivities that exceed those of monometallic Pd or Au catalysts; however, ascertaining the reasons for these differences remains a challenge. The formation of PdAu alloys modifies both the electronic and geometric structure of Pd, which has been demonstrated by investigations that involve X-ray photoelectron spectroscopy (XPS), X-ray absorption spectroscopy (XAS), , and Fourier transform infrared spectroscopy (FTIR) of adsorbed CO. ,,,,,,, These two effects are entangled and complicate the interpretation of data obtained by these methods, because the atomic composition and arrangement of PdAu alloy surfaces affect the electronic structure. Pd and Au are miscible and form a substitutional, exothermic alloy (−2 > Δ H mix > −9 kJ mol –1 ) for all compositions. As such, Monte Carlo simulations of PdAu surfaces predict the formation of significant numbers of isolated Pd monomers when the mole fraction of Au greatly exceeds that of Pd. Most results indicate that Pd atoms gain d-electrons as the Au contents in PdAu alloys increase.…”
Section: Introductionmentioning
confidence: 99%
“…The major technical challenge of the Pd–Au system is the preparation of homogeneously distributed Pd–Au alloy nanoparticles with high-phase purity. Employing nonuniform Pd–Au alloy nanoparticles has complicated this system and hampered the elucidation of the roles of Au and KOAc additives in the commercial catalyst. Indeed, Pd–Au alloys, such as Pd/Au(111) and Pd/Au(100), have been primarily used as model surfaces despite their distinct structures from the commercial catalyst (KOAc/Pd–Au/SiO 2 , Au/Pd = 1/4) .…”
Section: Introductionmentioning
confidence: 99%